Healthy Bus Drivers, Sustainable Public Transport: A Three-Time Repeated Cross-Sectional Study in Switzerland - Viviane Fiona Mathilde Remy; Irina Guseva Canu (Frontiers Media S.A., 2023)
Objectives: To study the change in the prevalence of bus drivers' health outcomes between 2010 and 2022 and their relationship with working conditions.Method: Unionized bus drivers completed a self-administered questionnaire in 2010, 2018, and 2022 on 13 health outcomes, sick leaves, and accidents and working conditions and their change during SARS-CoV-2 crisis. For outcomes which prevalence increased since 2010, we performed logistic regression models adjusted for covariates.Results: The study sample included 772 participants in 2010, 393 in 2018, and 916 in 2022. The most prevalent health problem (≥50%) was shoulder or neck muscle pain. The most tedious working conditions were working days over 10 h. Shoulder or neck pain, sleep disorders, sick leaves, and accidents increased since 2010 and were associated with working conditions, and co-morbidity. The SARS-CoV-2 pandemic had additional negative consequences.Conclusion: Most bus drivers' working and health conditions worsened in the last 12 years. Given the study design, the results deserve a cautious interpretation and generalization. Cohort studies should confirm these results and inform interventions targeting the most tedious and harmful working conditions.